ART AS CATHARSIS âWHATâS ON YOUR MIND?â SERIES - Paulina Tamara Syarief, Nadine
As social beings, humans find comfort in sharing their experiences. Through this pandemic, people tend to stay at home and rely on social media to interact with one another, but the lack of direct interaction has caused inner fatigue. If kept buried for too long then it will have a bad impact on life. This final project aims to channel those emotions by creating a series of paintings that highlight emotional journey during the pandemic. The theoretical approach used in explaining this work relates to the form of art theory as expression, catharsis, and symbolism. In general, the creation of this work is a form of outlet for negative thoughts that needs to be expresssed visually as though it is a journal or diary in the form of oil paint and other medias on a 3D canvas. The technique used in creating this work is the incorporation of both 2D and 3D elements. Although this type of expression does not involved other people, there is an unconsious urge to communicate these feelings to the public through paintings. The series is focused in the expression of overwhelming feelings which results in it being a work that focuses on expression, however there is sublimation or refinement of feelings through the making of this work. The sublimation is seen through the depiction of of objects and texts as another form of my feelings. The result of this final project includes 6 paintings that tells the story of negative feelings felt throughout the pandemic. Objects that appear in these artworks include a figure of a person with supporting objects done with oil paint, texts, and other materials such as paper as an extension of disclosing feelings, so it looks like a diary. Each canvas has different size, shape, and display to express different feelings